THE HIGHER FULLERENES - A CANDIDATE FOR THE STRUCTURE OF C78 - Fowler, P; Batten, R; Manolopoulos, D (1991)
A systematic search reveals five C78 fullerene cages with isolated pentagons, but only one with a closed electronic shell, as predicted by Fowler's leapfrog rule. The closed-shell isomer has D3h symmetry and is the most likely candidate for the structure of C78. Like C70, it corresponds to an expansion of the C60 structure by insertion of an equatorial belt of hexagons.